Toxicological assessment of omethoate insecticide in Allium cepa L. - Seher Karagol; Oksal Macar; Kültiğin Çavuşoğlu; Emine Yalçın (Scientific Reports)
Abstract This research provides a comprehensive understanding of the toxicity of omethoate, a widely used organophosphate pesticide, in a non-target test organism, Allium cepa L. In this study, the control group received distilled water, while the treatment groups were exposed to omethoate at concentrations of 2 mg/L, 3.1 mg/L and 5.7 mg/L for 72 h, respectively.At the end of the experimental period, physiological, cytogenetic, biochemical, and meristematic cell damage level analyses were carried out. Rooting ratio (%), root elongation, and weight gain in the omethoate-treated groups were notably reduced compared to the control. The degree of growth inhibition became more pronounced as the concentration of omethoate increased. Omethoate caused cytogenetic damage, considering the increased micronucleus, chromosomal aberrations, DNA damage, and decreased mitotic index levels compared to control group values. Chromosomal aberrations observed after omethoate exposure were ranked from most to least dense, such as sticky chromosome, vagrant chromosome, fragment, bridge, and unequal chromatin distribution. Omethoate treatment promoted a rise in both activities of superoxide dismutase and catalase and malondialdehyde levels, which are indicators of oxidative stress. Among the other biochemical parameters examined, proline level increased, and chlorophyll a and b levels decreased in omethoate-treated groups. The adverse effects on genotoxicity and biochemical parameters increased as the dose of omethoate increased. The disorders induced by omethoate pesticide in root tip meristem cells were epidermis cell damage, flattened nucleus, cortex cell damage, thickened cortex cell wall, and thickened conduction tissue. According to the findings of this study, omethoate is a chemical that causes multifaceted and dose-dependent toxicity in A. cepa.